THE ROLE OF THE STATE IN THE ISLAMIC ECONOMIC SYSTEM: A REVIEW OF ABBAS MIRAKHOR'S THOUGHT - Havis Aravik; Achmad Irwan Hamzani; Nur Khasanah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2021)
Islamic economy is a progressive and dynamic economy. Various new theories have been raised as an offer for the development of Islamic economics, one of which was carried out by Abbas Mirakhor. This article discusses the main principles of the economic system to the role of the state; an offer of Abbas Mirakhor to Islamic economics. To know more deeply the Islamic economic thoughts offered by Abbas Mirakhor, from the main principles of the economic system to the role of the state in the economy. This article uses a type of qualitative research using library research. The results of this study indicate that Abbas is a practitioner of Islamic economics and finance who has a good reputation in the world, both Islam and the West and is considered a reformer in the Islamic economy, and is part of the Iqtishad school of thought. In the field of the Islamic economic system, Mirakhor argues that the main principle of the Islamic economic system requires distribution in two mechanisms, namely freedom, and justice, without which prosperity will not be realized. Therefore, there is a need for a hermeneutical approach to answering various problems that occur in the Islamic economic system. In the context of the state, according to Mirakhor, the state has a very significant role in the welfare of society, especially through its productive policies. The state must also be present in realizing justice amid society.